ANALISIS DAMPAK LINGKUNGAN OPERASI PT TOBA PULP LESTARI DI WILAYAH HUTAN TANAM INDUSTRI MASYARAKAT ADAT PARGAMANAN BINTANG MARIA KECAMATAN PARLILITAN KABUPATEN HUMBANG HASUNDUTAN - Eflin Efridonda Simbolon; Artha Tobing; Dimpos Manalu (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
Forest resource management in Indonesia is an important part of sustainable development policy aimed at balancing economic growth, environmental sustainability, and community welfare. One form of forest utilization is through the Industrial Plantation Forest (HTI) scheme. However, in practice, HTI activities often generate various environmental and social impacts on communities living around forest areas. PT Toba Pulp Lestari is one of the companies managing Industrial Plantation Forests in Humbang Hasundutan Regency, including within the customary territory of the Pargamanan Bintang Maria Indigenous community in Parlilitan District. This study aims to analyze the environmental impacts of the company’s operations and to understand community perceptions of the environmental changes that have occurred. This study employs a qualitative method with a descriptive approach. Data were collected through interviews with key informants, including the leader of the indigenous community, community members directly affected by the company’s activities, and additional informants such as village government representatives and the company. Documentation studies were also used to support the data. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that the operations of PT Toba Pulp Lestari have caused various environmental changes, including a reduction in natural forest cover, decreased water availability, and disruption of ecosystem balance, which has affected the productivity of benzoin forests as the main livelihood source of the community. In addition, the community has experienced social and economic changes, such as shifts in livelihood patterns, reduced agricultural and forest yields, and differing views within the community regarding the presence of the company. Although the company provides employment opportunities for some community members, the economic benefits remain limited. The conclusion of this study shows that the operational activities of PT Toba Pulp Lestari have significant impacts on the environment and the livelihoods of the Pargamanan Bintang Maria Indigenous community. Therefore, more sustainable forest management is required by considering environmental conservation, protection of indigenous peoples’ rights, and stronger government supervision to create a balance between economic development and environmental sustainability